In-situ polymerization of diacetylene ligands for applications in quantum dot solar cells - Gregory, DAF (2021)
Improving the efficiency of next-generation solar cells is crucial to their commercialization. This thesis presents a novel approach to coupled organic-inorganic nanostructures through in-situ polymerization of a ligand, creating an extended, delocalized sp2 environment surrounding lead sulfide (PbS) quantum dots in a thin film.